Handoff Technique Using LoRaWAN Technology - Manalu, Istas Pratomo; Sigiro , Marojahan Mula Timbul; Sinambela , Eka Stephani; Simatupang , Frengki; Kasih , Winda; Tampubolon , Benni; Hutabarat , Alexandro (SOTVI, 2025)
This research introduces an innovative handoff methodology for LoRaWAN in IoT systems. This approach, validated through empirical testing, not only markedly enhances connection quality but also facilitates the system in selecting the optimal gateway, providing redundancy, verifying gateway availability prior to handoff, and managing handoff failures. Experimental evaluations were performed using two LoRa gateways (Arduino Nano and LoRa RFM95) and a single LoRa end device (comprising Arduino Nano, LoRa RFM95, MQ135 sensor, and OLED), during which the node transitioned between two positions (Gateway A and Gateway B) approximately 500 meters apart. Handoff was triggered when one RSSI value fell below the other. The experimental handoff threshold was established at an RSSI of -93 dB; exceeding this value resulted in the transmitter losing service from the gateway. During the experiment, the transmitter gradually moved from Gateway A to Gateway B over a period of 40 seconds. At the 20th second, a critical juncture was observed wherein the RSSI and SNR values of Gateway B gradually exceeded those of Gateway A. Gateway B recorded an RSSI of -92 dBm and an SNR of 4 dB, whereas Gateway A recorded an RSSI of -97 dBm and an SNR of 2 dB. This signifies that Gateway B exhibited superior signal quality. Based on a dynamic comparison of these parameters, the system effectively executed a handoff at the midpoint, thereby redirecting data transmission to the gateway with the higher link quality.